Annotated catalogue of chameleon types in the collection of the Natural History Museum, UK (NHMUK) (Reptilia: Squamata: Chamaeleonidae) - Campbell, Patrick D; Denzer, Wolfgang (Zootaxa, 2020)
We provide a list of type specimens of chameleons present in the collection of the Natural History Museum in London for the first time, including their associated collection numbers. Currently the collection contains 54 primary types (29 holotypes, two lectotypes and 23 syntype series plus two syntypes where the type status is in doubt) as well as numerous secondary types for 12 species (nine paratype and three paralectotype series). Type material present in the collection represents 39 valid chamaeleon taxa.